The Use of Oral Sucrose for Procedural Pain Relief in Infants Up to Six Months of Age: A Randomized Controlled Trial - Wilson, Sally; Bremner, A.; Mathews, J.; Pearson, D. (Elsevier, 2012)
The aim of this study was to evaluate the effectiveness of oral sucrose in decreasing pain during minor procedures in infants of 1-6 months corrected age. A blinded randomized controlled trial with infants aged 4-26 weeks who underwent venipuncture, heel lance or intravenous cannulation were stratified by corrected age into >4-12 weeks and >12-26 weeks. They received 2 mL of either 25% sucrose or sterile water orally 2 minutes before the painful procedure. Nonnutritional sucking and parental comfort, provided in adherence to hospital guidelines, were recorded. Pain behavior was recorded using a validated 10 point scale at baseline, during and following the procedure. Data collectors were blinded to the intervention. A total of 21 and 20 infants received sucrose and water, respectively, in the >4–12-week age group, and 21 and 22, respectively, in the >12–26-week age group. No statistical differences were found in pain scores between treatment and control groups at any data collection points in either age group. Infants aged >4-12 weeks who did nonnutritional sucking showed statistically significantly lower median pain scores at 1, 2, and 3 minutes after the procedure than those who did not suck. Infants aged >4-26 weeks exhibited pain behavior scores that indicated moderate to large pain during painful procedures; however, there was insufficient evidence to show that 2 mL 25% sucrose had a statistically significant effect in decreasing pain. Infants should be offered nonnutritional sucking in compliance with the Baby Friendly Health Initiative during painful procedures.